Christian Arabic Apologetics during the Abbasid Period (750-1258). - Samir Khalil Samir; Jorgen Nielsen (Editors) (Numen Book Series, 1994)
During the first six-seven centuries of the Islamic era there was a very lively exchange between Christian and Islamic thinking. It was a period when Christian theologians of various denominations had to find ways of expressing their traditional ideas in Arabic. In the process their thinking developed. The papers in this volume represent the wide range of this field, including detailed studies of such key writers as Abū Rā'itah, Yaḥyā born 'Adī and Theodore Abū Qūrrah, as well as probably the earliest, anonymous, Christian apology in Arabic. The Islamic context in which such writers worked is also dealt with, as is the wider geographical spread of Christian Arabic thought extending to Islamic Spain.